Social and Political Perceptions of the Borat Phenomenon in Kazakhstan: Evidence from a Case Study of University Students - Ó Beacháin, Donnacha (Studies of Transition States and Societies, 2011)
This article begins by chronicling and evaluating the reaction of the government of Kazakhstan to Sacha Baron Cohen’s ﬁ lm Borat—Cultural Learnings of America for Make Beneﬁ t Glorious Nation of Ka zakh stan. It then compares and contrasts the oﬃ cial government reaction with the expressed attitudes of local members of Kazakhstan’s young English-speaking elites. This study is based on the results of a survey of almost ﬁ ve hundred young university students conducted in March 2007 at the Kazakhstan Institute of Man age ment, Economics and Strategic Research (KIMEP), the most prestigious university in the country. The sample gives a snapshot of those most likely to have been aware of Borat - the young, internet-savvy, educated urban elite - and inter alia provides insights into how respondents in Kazakhstan thought the movie impacted their country and would inﬂ uence how they were treated abroad. The survey results suggest that while responses to Borat were heterogeneous, most students accepted that the choice of Kazakh stan as a target for satire was coincidental rather than conspiratorial. Despite oﬃ cial eﬀ orts to ban the movie, a majority of the respondents had seen the ﬁ lm and believed that the ban was a mistake. Also, while recognising that Borat would raise Kazakhstan’s proﬁ le in the world, respondents doubted it would increase knowledge, and some feared a change in their treatment when travelling abroad.